// 递归法 function createArr(m,n){ var arr=[]; function addEle(count,ele){ if(count!=0){ arr.push(ele) count=count-1; addEle(count,ele) } } addEle(m,n) return arr } console.log(createArr(4,'c'))
// 字符串法 function createArr1(m,n){ return Array(m).join(',').split(',').map(()=>n) } console.log(createArr1(5,'b')) // es6法 let fun = (m,n)=> new Array(m).fill(n); console.log(fun(10,'c'))
let fun1 = (m,n)=> Array.apply(null,new Array(m)) .map(()=>n) console.log(fun1(6,'d'))
let fun2 = (m,n)=>Array.from(new Array(m),item=>n) console.log(fun2(6,'d'))